REINTERPRETING NURCHOLISH MADJID’S THEORIES OF SECULARIZATION: REAPPLYING THESE THEORIES TO INDONESIA’S CONTEMPORARY ISLAMIC EDUCATION CURRICULUM - Ulya, Vita Fitriatul; Abu Bakar, M. Yunus; Masud, Ali (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
This study examines how Nurcholish Madjid’s theories on secularization have been reinterpreted and their impact on Indonesia’s current Islamic curriculum. Madjid’s perspective on secularization is not a rejection of religion but rather a process that can strengthen faith and foster a more inclusive educational system. Using a qualitative literature review, the research demonstrates how Madjid’s concepts of separating religious and political authority can serve as a foundation for a curriculum that integrates general knowledge with Islamic values. This approach aims to cultivate students critical thinking and tolerance. The findings highlight the relevance of Madjid’s ideas to contemporary issues in Indonesia, such as globalization and pluralism. The study concludes with recommendations for curriculum development aligned with Madjid's philosophy and advocates for further research into the practical application of his concepts in educational settings. Ultimately, this research contributes to understanding how Islamic education can adapt to a modern, multicultural society while maintaining its spiritual core.